Molecular Mechanisms and Drug Development in Aquaporin Water Channel Diseases: Aquaporins in the Brain - Hideyuki Kobayashi; Toshihiko Yanagita; Hiroki Yokoo; Akihiko Wada (Elsevier, 2004)
Water homeostasis of the brain is essential for its neuronal activity. Changes in water content in the intra- and extra-cellular space affect ionic concentrations and therefore modify neuronal activity. Aquaporin (AQP) water channels may have a central role in keeping water homeostasis in the brain. Among AQP subtypes cloned in mammalian, only AQP1, AQP4, and AQP9 were identified in the brain. Changes in AQP expression may be correlated with edema formation of the brain. In this review, we describe the physiological function of AQPs and the regulatory mechanism of their expression in the brain. Keywords:: aquaporin, brain, edema, glucocorticoid, lipid raft